Natural gas extraction and community development in Tanzania: Documenting the gaps between rhetoric and reality. Issue 3 (July 2019) - Kamat, Vinay R.; Le Billon, Philippe; Mwaipopo, Rosemarie; Raycraft, Justin
Highlights: The rhetoric of gas-driven prosperity has not translated into reality for the gas project-affected communities. Despite protests and litigation, the compensation rate offered to the project affected people in the study villages remains minimal. Government officials and company representatives must foster multi-directional lines of communication with affected communities. A network of stakeholders must be formed to document, monitor and analyze the on-going impact of the gas project on affected communities. Longitudinal research is needed to document and analyze the long-term impacts of the gas project on affected communities. Abstract: The Tanzanian government recently adopted new legislations to reform its oil and gas sector, for the purpose of safeguarding its interests and serving the developmental aspirations of its ordinary citizens. While laudable in spirit and content, these reforms have raised questions about their implementability, particularly with regard to their developmental impact on all Tanzanians. Drawing on fieldwork conducted in the natural gas producing coastal region of Mtwara, including a large-scale household survey, this paper contrasts policy articulations with local community expectations and household perceptions, attending to the different ways in which gas development activities have affected communities near on-shore gas fields and gas processing plants. While the rhetoric of gas-driven prosperity has contributed to high expectations among communities in the gas producing region, it has not translated into reality for most individual households. This gap reflects the centralized character of resource governance, the inconsistent way policies pertaining to natural gas development have been framed and reframed, the unrealistic expectations of prosperity that have pervaded national and local discourses on the gas discoveries, the lack of public consultation, and state-directed violence. The paper contributes empirically to the literature and on-going debates about the extractive sectors' impacts on project-affected communities.